2012
DOI: 10.1038/srep00756
|View full text |Cite
|
Sign up to set email alerts
|

High-performance method for specific effect on nucleic acids in cells using TiO2~DNA nanocomposites

Abstract: Nanoparticles are used to solve the current drug delivery problem. We present a high-performance method for efficient and selective action on nucleic acid target in cells using unique TiO2·PL-DNA nanocomposites (polylysine-containing DNA fragments noncovalently immobilized onto TiO2 nanoparticles capable of transferring DNA). These nanocomposites were used for inhibition of human influenza A (H3N2) virus replication in infected MDCK cells. They showed a low toxicity (TC50 ≈ 1800 μg/ml) and a high antiviral act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 41 publications
(55 reference statements)
0
21
0
1
Order By: Relevance
“…They prepared a DNA/polylysine conjugate, where the positively charged polylysine is used to anchor on titania surface and the DNA fragment can hybridize to its complementary strand. 18,19 To make the attachment chemistry more cost-effective, it is desirable to directly adsorb nonmodified DNA. Zhu et al studied the adsorption of calf thymus DNA by TiO2 NPs and they concluded that phosphate is responsible for DNA adsorption based on IR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…They prepared a DNA/polylysine conjugate, where the positively charged polylysine is used to anchor on titania surface and the DNA fragment can hybridize to its complementary strand. 18,19 To make the attachment chemistry more cost-effective, it is desirable to directly adsorb nonmodified DNA. Zhu et al studied the adsorption of calf thymus DNA by TiO2 NPs and they concluded that phosphate is responsible for DNA adsorption based on IR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…The antiviral activity of the Si–NH 2 ·ODN(4) nanocomplex was not inferior to that of the TiO 2 ·PL–ODN nanocomplexes reported in our previous papers [2022]. The high inhibition efficiency of the virus reproduction with the use of the Si–NH 2 ·ODN nanocomplex is provided by the fact that the nanocomplex delivers ODN into the cytoplasm of the cell, and ODN can penetrate into the cell nuclei (Fig.…”
Section: Resultsmentioning
confidence: 63%
“…The experiments were carried out similarly as described in [20]. In short: Two days after the formation of a continuous monolayer of MDCK cells at 37 °C and 5% CO 2 , the cells were washed with nutrient medium without serum.…”
Section: Methodsmentioning
confidence: 99%
“…Many researches choose the same segment to study antiviral activity of nucleic acid-based drugs [e.g., 12]. At first, it was shown that TiO 2 •PL-DNA and TiO 2 •PL±DNA nanocomposites showed a low toxicity (TC 50 1500 g/ml) in the MDCK cell culture [13,14]. To inhibit the reproduction of IAV, we used the nontoxic concentration of the nanocomposites (5 g/ml) corresponding to 0.1 μM for oligonucleotides (20 nmol/mg).…”
Section: Resultsmentioning
confidence: 99%